1983
DOI: 10.1145/322358.322370
|View full text |Cite
|
Sign up to set email alerts
|

The Expressiveness of Simple and Second-Order Type Structures

Abstract: Typed lambda (?`-) calculi provtde convement mathematical settings in which to investigate the effects of type structure on the function definmon mechamsm m programming languages. Lambda expressaons mtm~c programs that do not use while loops or carcular function definitions. Two typed ?`-calculi are investigated, the sunply typed ?`-calculus, whose types are similar to Pascal types, and the second-order typed ?,-calculus, which has a type abstractaon mechamsm simdar to that of modern data abstraction languages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
1

Year Published

1984
1984
1996
1996

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(42 citation statements)
references
References 31 publications
(36 reference statements)
2
39
1
Order By: Relevance
“…This corollary generalizes one direction of results obtained by Girard [14], and Fortune, Leivant & O'Donnell [12], and Leivant [17,18] which may be summarized as "The number-theoretic functions representable in F n are exactly the functions provably recursive in n th -order arithmetic." The induction principle will look more familiar after we curry at the argument V to eliminate the dependent pair and also apply uniform parameterization over the argument A.…”
Section: £(Ps* a ) = £(Pz Xs{a) ) •supporting
confidence: 75%
See 1 more Smart Citation
“…This corollary generalizes one direction of results obtained by Girard [14], and Fortune, Leivant & O'Donnell [12], and Leivant [17,18] which may be summarized as "The number-theoretic functions representable in F n are exactly the functions provably recursive in n th -order arithmetic." The induction principle will look more familiar after we curry at the argument V to eliminate the dependent pair and also apply uniform parameterization over the argument A.…”
Section: £(Ps* a ) = £(Pz Xs{a) ) •supporting
confidence: 75%
“…Closely related is work by Girard [13,14], Fortune, Leivant & O'Donnell [12], and Leivant [17,18] who are concerned with the relationship between higher-order logic and polymorphic A-calculi.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting system is a variant (the "Curry version" in the terminology of [8]) of the polymorphic second-order lambda calculus independently due to [37] On the Church numerals, many computable functions can be represented by terms of type N at-»N at. The next result is due to [36]; see also [34].…”
Section: E F I N I T I O Nmentioning
confidence: 88%
“…functions may be the key to a novel programming style. They have studied an austere subset of the language we are considering in which the fixpoint operator fix is excluded, and have shown that this restricted language has extraordinary properties [32,33]. On the one hand, all expressions have normal forms, i.e.…”
Section: B Explicit Polymorphismmentioning
confidence: 99%